ANALISIS KELAYAKAN USAHATANI KANGKUNG AIR (STUDI KASUS DI DESA PLANGKAPAN, KECAMATAN TAMBAK, KABUPATEN BANYUMAS) ECONOMIC ANALYSIS OF KANGKUNG AIR'S FARM (CASE STUDY ON DESA PLANGKAPAN, KECAMATAN TAMBAK, KABUPATEN BANYUMAS) - Yekti, Ananti (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
The aim of this study was focussed on three main parts: labour absorption and productivity, farmer income, profitability and household welfare level the research conducted on Desa Plangkapan, Kecamatan Tambak, Kabupaten Banyumas. The method of sample selection was simple random sampling with 30 respondents who planted kangkung air during Octobre 2004 April 2005. The result of the study showed that kangkung air-farm is profitable. It showed by the value of R/C ratio, rentability and labour absorption, which are higher than standart value. By the kangkung air-farm, household farmer welfare level was not to be poor again